Pemanfaatan Buku KIA Terhadap Pengetahuan Ibu dan Anak Di Posyandu Melati, Kecamatan Marelan - Aulia Febrina (Syntax Corporation Indonesia, 2022)
The MCH Handbook is a Maternal and Child Health Book. Usually, most people call it the “pink book”, according to the color. The book contains maternal health records. Starting from notes containing information on pregnancy, childbirth and postpartum. Citing the official website of the Indonesian Ministry of Health, the maternal and child health book or MCH handbook is a guide to information and health records during pregnancy, childbirth and children aged 6 years. The contents of the book are very important to monitor health and record anyabnormalities in the mother and child. The recording of the MCH book is related to the health status of the mother and child, so it requires the participation of the mother to assess the completeness of the MCH book notes. It is necessary to increase the recording of the completeness of the MCH handbook by health workers because the results of the recording can be related to MCH knowledge. The benefits of the MCH Handbook are not only in the health sector, but have been integrated with other sectors, including a birth certificate to make it easier to get a certificate, a handbook for the Family Hope Program companion, as a medium for monitoring the growth and development of children in PAUD, Bina Keluarga Toddler.